Mediações musicoterapêuticas na educação: ampliando a compreensão sobre as dificuldades de aprendizagem em leitura - Brasil, Elisama Barbosa (2012)
This research was conducted in the Music School and Performing Arts Postgraduate Program/UFG, in the research line Music, Education and Health of the Master's Degree in Music. We attempted to investigate normative children with learning difficulties in reading, proposing music therapeutic actions as mediation to expand the understanding of these cases. The field research, a case study of qualitative approach, was developed in an elementary public school in the city of Goiania, through which data were collected in many ways: music therapeutic visits to the learners, semi-structured interviews with teachers, student's family and the school context observations. The analysis was performed using data triangulation, establishing three periods (Beginner, Intermediate and Final) considering the musical sound expressions and the inter-and intrapersonal relationship aspects of these students and the perceptions aspects of the other actors (teachers and family members), and data on the dynamics of the school, generating analytical categories. The theoretical framework that subsidized this analysis was the Complexity Theory in dialogue with theoretical references of the music therapy, education and socio-historical psychology. The results of research showed that the homogeneity characteristic of the teaching/traditional school can lead to noncompliance of the students in situations of free expression and/or creative character, tending to the manifestation of misconduct and disorder. We understand, according to the complexity, that the disorder is a necessary phenomenon and concomitant to the order, since you need to learn to build, rebuild and/or deconstruct ideas, experiences and values. Music therapy in the school allowed a space for expression of the relations and intrapersonal and interpersonal conflicts of learners. We believe that, to provide significant new experiences the subject (and do experiment) therapeutic musicians from experience, it is possible to facilitate to internalization of new knowledge and, consequently, the development. Complexity theory has enabled the contextualization of learning disabilities in reading favoring the understanding of the multiple factors that are mutual.